Exploring the Use of Code-Switching in EFL Undergraduate Classroom Interactions - Haq, Muhammad Amiq Nur Dinil; Ghozali, Imam; Nugraheni, Dyah Ayu (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
The research aims to investigate the types and reasons for code-switching among EFL students during classroom interactions. Utilizing a descriptive qualitative methodology, the study analyzed classroom interactions among eleven fifth-semester students that had been selected using purposive sampling method at a Private University in Jember. Data collection tools for this research included observation and interview. After being collected, the data then were analyzed by using the framework of Miles and Huberman (1994). The study revealed three types of code-switching: tag switching, intra-sentential switching, and inter-sentential switching. The primary reasons for code-switching included enhancing mutual understanding, ensuring effective communication, expressing emotions and opinions accurately, navigating linguistic identities, and showing respect and solidarity. The findings reveal distinct patterns of code-switching among participants: tag-switching involves inserting tags at the end of an utterance; intra-sentential switching occurs within a sentence, at its beginning, middle, or end; and inter-sentential switching involves switching languages between sentences. There are several reasons why students engage in code-switching. These include difficulties in using English fluently, switching languages out of respect and to show solidarity as students, and to better express their emotions and opinions. Future studies should consider larger and more diverse samples, multiple institutions, and a balanced exploration of both positive and negative aspects of code switching in academic settings.